Towards energy efficiency and power trading exploiting renewable energy in cloud data centers - Aslam, Shahzad; Aslam, Sheraz; Herodotou, Herodotos; Mohsin, Syed Muhammad; Aurangzeb, Khursheed (My University, 2020)
This study investigates the energy cost and carbon emission reduction problem in geographically distributed cloud data centers (DCs), where each DC is connected with its own renewable energy resources (RERs) for green energy generation. We consider four cloud DCs that are operated by a single cloud service provider. They consume energy from both RERs and from the commercial grid to meet the demand of cloud users. For energy pricing, we consider four different energy markets that offer varying energy prices per hour. Additionally, our proposed strategy enables DCs to sell excess electricity to the commercial grid in peak-price hours and purchase in low-cost hours according to power trading. This work also exploits energy storage devices (ESDs) to store energy for future use. We utilize real-time data requests, weather data, and pricing data for performing simulations and results affirm the effectiveness and productiveness of our proposed method to mitigate the energy cost and carbon emission of cloud DCs.
Keywords: Cloud computing; Cloud data centers; Energy efficiency; Power trading; Renewable energy integration